Pengaruh Karakteristik Konsumen Terhadap Intensitas Pembelian Madu Suhita - Kertayoga, IPAW; Desfaryani, Rini; Kusmaria, Kusmaria; Irawati, Luluk (Journal of Food System & Agribusiness, 2023)
Indonesia has considerable potential in the development of honey cultivation because it is supported by tropical climate factors and forest resources that can be used as honey beekeeping ecosystems. In 2021, honey production increased by 269.55% compared to the previous year, but this is still not able to meet the demand of the domestic market, whose consumption level is around 40-60 grams/per capita/per year. Referring to this condition, the honey industry in Indonesia has a large and prospective market so entrepreneurs and producers are starting to emerge in this industry. In maintaining its dominance in Bandar Lampung and with the potential to expand to other areas, Madu Suhita needs to know what characteristics of its current consumers are like and what factors of consumer characteristics influence their purchasing intensity for Madu Suhita products. This research was conducted in Bandar Lampung, that is at the Madu Suhita outlet. In this study, descriptive analysis was used to analyze the characteristics of Madu Suhita consumers. The result of this research is that the consumer characteristics of Suhita Honey that have a positive influence on the purchase intensity of Suhita Honey is the level of income, while other variables from consumer characteristics such as gender, age, and education level do not have a significant effect on purchase intensity.